1999
DOI: 10.1039/a903113h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a direct current gas sampling glow discharge ionization source for the time-of-flight mass spectrometer

Abstract: A direct current, reduced-pressure, gas sampling glow discharge (GSGD) ionization source has been developed and interfaced to an orthogonally extracted time-of-flight mass spectrometer for the purpose of generating both atomic and molecular fragmentation mass spectra. The discharge is contained within the first vacuum stage of the differentially pumped interface of the mass spectrometer. The source is mechanically and logistically simple to construct, operate, and maintain. Switching between the atomic and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Glow discharge has been used extensively for ionization in the analysis of inorganic solids and organic compounds 18–20. The atmospheric sampling glow discharge ionization (ASGDI) source supported by untreated atmospheric gases was introduced as an ionization source for organic compound analysis 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Glow discharge has been used extensively for ionization in the analysis of inorganic solids and organic compounds 18–20. The atmospheric sampling glow discharge ionization (ASGDI) source supported by untreated atmospheric gases was introduced as an ionization source for organic compound analysis 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Ionization occurs when the DART gas makes contact with the sample in the open gap between the DART source outlet and the orifice of the mass spectrometer. However, other glow discharge ionization techniques [20,21] operate by introducing sample vapor through an orifice into a glow discharge region at reduced pressure. Unlike DART, possible sample loss could occur when introduced into a vacuum, and sample damage is possible on direct exposure to an electrical discharge.…”
mentioning
confidence: 99%
“…The authors obtained mass spectra dominated by the molecular parent ion, and reported impressive limits of detection from 1 to 2 ng/L for 2,4,6-trinitrotoluene and a linear dynamic range spanning more than six orders of magnitude [197]. Guzowski et al [199] coupled a similar device, a direct current gas sampling glow discharge (GSGD), to a TOFMS; Fig. 14 shows the GSGD-MS interface used in the work.…”
Section: Reduced-pressure Plasmas As Tunable Ion Sourcesmentioning
confidence: 97%
“…The Macor sleeve restricts the discharge to the region between the cathode and the grounded skimmer. The discharge is contained within the first vacuum stage of the mass spectrometric interface [reproduced from [199] with permission].…”
Section: Reduced-pressure Plasmas As Tunable Ion Sourcesmentioning
confidence: 99%